(untitled) (Rudarsko-geološko-naftni zbornik, 2020)
Middle Triassic deposits in the Karst Dinarides (south Lika area, near Gračac) were investigated for petrological, sedi- mentological and biostratigraphic determinations. Within two continuously recorded sections of sedimentary carbon- ates and interlayered pyroclastic rocks (Mali Kunovac and Kunovac sections) reflecting variable sedimentary-magmatic environments, valuable cephalopod fauna ranging from the middle Illyrian to the upper Illyrian age was found. The most significant was the recovery of the ammonoids Asseretoceras sp., indicating the upper part of the Illyrian Paraceratites trinodosus Zone, and Reitziites reitzi species which marks the upper part of the Illyrian Reitziites reitzi Zone. The dis- covery of the Reitziites reitzi species was not known from the Karst Dinarides until this finding.